Exposure to low outdoor temperature in the midtrimester is associated with low birth weight - (:unkn) unknown (BLACKWELL PUBLISHING, 2004)
Background: Although seasonal variation of birth weight has been reported previously, contributing factors such as the meteorological factor and its specific period of exposure remain unclear. Aim: To investigate the effect of season on birth weight and to determine the meteorological factor and its specific period of exposure which can contribute to any seasonal variation in birth weight. Methods: Retrospective analysis of 3333 singleton live births after 36 completed weeks of pregnancy. Maternal age, parity. route of delivery, sex and individual meteorological variables for the first, second, and third trimesters of each pregnancy were analysed using multiple regression analysis with the birth weight as the dependent variable. Results: A seasonal pattern was observed with lowest birth weights in women who had their last menstrual periods in summer and autumn. Upon multiple regression analysis, sex, parity, mode of delivery, and the temperature which the mother was exposed to in the second trimester were the independent determinants of birth weight. Conclusion: Exposure to low outdoor ambient temperature in the midtrimester can be associated with low birth weight.
Keywords: birth weight; humidity; meteorological factor; season; temperature; SEASONAL-VARIATION; INSULIN; PLASMA; SIZE; PREGNANCY; CHILDREN; CLIMATE; GROWTH; JAPAN